Effects of organic, hydraulic and fat shocks on the performance of UASB reactors with intermittent operation - Nadais, H.; Capela, I.; Arroja, L.; Duarte, A. (Water science and technology, 2001)
Three lab-scale UASB reactors operated at 35°C in an intermittent mode were subject to different step shocks: hydraulic, organic and feed fat content. The results show that the reactors have good resistance to the applied shocks and suggest that a feedless period is beneficial to the performance of the reactors, due to stabilisation of accumulated organic matter.